The Effects of Mesenchymal Stem Cell on Colorectal Cancer - Jintao Yuan; Zhiping Wei; Xinwei Xu; Dickson Kofi Wiredu Ocansey; Xiu Cai; Fei Mao (Stem Cells International)
Colorectal cancer (CRC) is a common malignant tumor of the gastrointestinal tract with nonobvious early symptoms and late symptoms of anemia, weight loss, and other systemic symptoms. Its morbidity and fatality rate are next only to gastric cancer, esophageal cancer, and primary liver cancer among digestive malignancies. In addition to the conventional surgical intervention, other therapies such as radiotherapy and chemotherapy and new treatment methods such as biologics and microbiological products have been introduced. As a promising cell therapy, mesenchymal stem cell (MSC) has attracted extensive research attention. MSCs are early undifferentiated pluripotent stem cells, which have the common features of stem cells, including self-replication, self-division, self-renewal, and multidirectional differentiation. MSCs come from a wide range of sources and can be extracted from a variety of tissues such as the bone marrow, umbilical cord, and fat. Current studies have shown that MSCs have a variety of biological functions such as immune regulation, tissue damage repair, and therapeutic effects on tumors such as CRC. This review outlines the overview of MSCs and CRC and summarizes the role of MSC application in CRC.